The Impact of the Skin Microbiome and Oxidative Stress on the Initiation and Development of Cutaneous Chronic Wounds - Manuela Martins-Green; Jane Kim; Klara Aziz (Antioxidants)
Wound healing is a very complex process composed of several phases in which precise events occur, both temporally and specially. However, when these processes go awry, biofilm-forming bacteria become installed in the healing tissue, and the patient has comorbidities, so the wounds do not heal and become chronic. In this review, we describe the importance of high levels of oxidative stress (OS) and bacteria from the skin microbiome in the initiation and development of chronic wounds. The skin microbiome is diverse in humans, and its composition is dependent on the environment in the specific areas of the body. OS is critical for wound healing as it stimulates the immune system to destroy pathogens and secrete cytokines and growth factors that stimulate healing. When OS levels become high in the wound and the bacteria of the skin install themselves in the wound, chronicity ensues. However, neither OS nor the bacteria of the skin alone can initiate chronicity. However, when present together, chronic wounds develop. Given the complexity of chronic wound initiation, developing treatment for these wounds has been difficult. Here, we also discuss the challenges of treating chronic wounds and offer a potential sequence of approaches to treating these wounds after debridement.